Southwest Research-Extension Center: 50 Years of Progress (Kansas Agricultural Experiment Station Research Reports, 1957)
The Garden City Branch Experiment Station has served the people of Kansas during the past 50 years (1907-1957). This publication is intended to present a historical report of the establishment of the station, its progress, projects, and personnel.
Keywords: 1957; SRP007; crops; soil; irrigation; dairy cattle; insects; Garden City